Descriptive: Interactive 3D Shape Modeling from A Single Descriptive Sketch. (November 2020) - Bobenrieth, Cédric; Cordier, Frédéric; Habibi, Arash; Seo, Hyewon
Abstract: In this paper, we present a sketch-based modeler that reconstructs a 3D shape by combining a single descriptive sketch and minimal user intervention. The user provides a single 2D drawing in the form of a descriptive sketch, where solid curves describe the visible silhouette, and dashed curves the hidden outline. The curves are partitioned into a set of closed curves in a semi-automatic manner, each of which is consolidated into a closed surface element by solving a constrained optimization problem. The final 3D shape is generated by assembling these surface elements. The algorithmic reconstruction is complemented by allowing users to optionally guide the shape computation or correct any inaccuracy. This is done by successively specifying different kinds of local constraints on sparsely selected points in rotated views, such as adjustment of volume thickness along the projection line, or curvature discontinuity. Consequently, the range and complexity of shapes that can be created from a single-view sketch are significantly extended. We evaluate our solution by reconstructing a wide range of 3D models from sketches of various sources, and visually comparing the reference models and the shapes reconstructed by users. Graphical abstract: Highlights: Using descriptive style to enable the shape modeling from a single sketch. Extends the range and complexity of shapes that can be created from a sketch. No limitation on the nature of the object or the viewpoint of the sketch.